From Industry to Culture: Regeneration of Golden Horn as a “Cultural Valley” - Bosson, Ceyda Bakbaşa; TÖRE, EVRİM ÖZKAN (Deniz Yengin, 2019)
The image shifts from industrial identity to cultural identity since 1980s in Golden Horn, one of Istanbul’s former industrial areas, encompassed cultural policies and urban regeneration processes in the area. This study discusses the positions of public and private sector investments in the region during the process of creating "The Golden Horn Cultural Valley" and reveals the policies that managed this regeneration. The research uses a multi-dimensional method considering both qualitative and quantitative data throughout economics, politics/urban cultural policies, society, culture and space. With respect to the projects, the authors highlight three main outcomes: (1) processes vary according to the actors, (2) lack of integrated vision and (3) disconnected cultural visibility.

1980'lerden bu yana sanayi kimliğinden kültürel kimliğe geçiş, İstanbul'un eski sanayi bölgelerinden biri olan Haliç'te, bölgedeki kültürel politikaları ve kentsel dönüşüm süreçlerini kapsamıştır. Bu çalışma “Haliç Kültürü Vadisi” oluşturma sürecinde bölgedeki kamu ve özel sektör yatırımlarının konumlarını tartışmakta ve bu yenilenmeyi yöneten politikaları ortaya koymaktadır. Araştırmada, ekonomi, siyaset/kentsel kültür politikaları, toplum, kültür ve mekan üzerine hem nitel hem de nicel verileri dikkate alan çok boyutlu bir metodoloji kullanılmaktadır. Projelerle ilgili olarak, yazarlar üç ana çıktının altını çizmektedir: (1) süreçler aktörlere göre değişmektedir, (2) entegre vizyon eksikliği söz konusudur ve (3) kültürel görünürlükte kopukluklar belirlenmiştir.
Sanayi̇den Kültüre: Hali̇ç’i̇n “Kültür Vadi̇si̇”ne Dönüşümü
Keywords: Post-industrial Space; Entrepreneurialism; Golden Horn; Culture-led Regeneration; Urban Policies